In situ simulation training in First Aid. Pilot study. First aid in a dangerous workplace - Grzegorz Witkowski; Olga Padała; Wojciech Dzikowski; Katarzyna Naylor; Ewa Domańska-Glonek; Anna Torres; Kamil Torres (Kazimierz Wielki University, 2017)
Abstract Purpose The aim of the study was to evaluate the newly develop course prepared for the employees working in the forest and mountain environment Methodology 31 people participated in the course. They were employees of Roztocze National Park and the Forestry Commission Lutowiska. A diagnostic survey was implemented in a form of a questionnaire. The respondents were provided with two original questionnaires and a telephone survey. Surveys were anonymous and voluntary. Findings The average assessment of First Aid knowledge before the workshop was 2.48 and majority of participants assesed First Aid as difficult. After the workshop, the respondents assessed the knowledge on average as 3.87 and as much as 58% declared that definitely would provide First Aid to a stranger; 81% to a close person. Over 80% of respondents noticed the need of  regular training in First Aid. Research implication The analysis showed that regular improvement of First Aid skills is required by the participants. The training should be adjusted to the group's needs in terms of the program, teaching techniques and the place of training. There is a need to implement such training on a wider scale among forestry and mountain workers. Originality Uncovering the gaps in First Aid training in mountain and forest workers in their professional training.